PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BARITO KUALA - Hamidah Hamidah (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2019)
The purpose of this study is to find out how the implementation of Occupational Safety and Health (K3) in the Office of Public Works and Spatial Planning of Barito Kuala Regency, what obstacles are faced by the Office of Public Works and Spatial Planning of Barito Kuala Regency in the implementation of Occupational Safety and Health (K3) in the field, and efforts made by the Barito Kuala District Public Works Office to face obstacles in the implementation of Occupational Safety and Health (K3). The research method uses a qualitative approach to the type of descriptive research. Data collected by interview and documentation. The sample is determined using a purposive sampling technique that is setting informants by determining from the beginning of the study the number of people with the desired characteristics. Data analysis uses deductive data analysis. The results showed that 1) Implementation of Occupational Safety and Health (K3) in the Office of Public Works and Spatial Planning of Barito Kuala Regency included the initial steps and further steps, 2) Obstacles faced by the Department of Public Works and Spatial Planning of Barito District in the Implementation of Occupational Safety and Health (K3) influenced by 3 (three) factors, namely: human factors (HR), material factors (tools and machines), as well as natural and environmental factors, 3) Efforts made by the Office of Public Works and Spatial Planning of Barito Kuala Regency to overcome barriers in the implementation of Occupational Safety and Health (K3), among others, provide training and development on occupational safety and health (human factors), repair equipment that is damaged but still suitable for use, and replace equipment that is already completely unfit for use (material factor ) and place workers to regulate the flow of traffic in the project environment, and provide an appropriate PPE that is intended for the health of protected workers (natural and environmental factors).